THE EFFECT OF MARKETING MIX ON CUSTOMER LOYALTY INDONESIAN SHARIA BANK IN BANDA ACEH WITH SATISFACTION AS AN INTERVENING VARIABLE - Zahriatul Aini (UPT Publikasi Ilmiah UNISBA, 2025)
This study explores the impact of the marketing mix on customer loyalty at the Banda Aceh Branch of Bank Syariah Indonesia (BSI), with satisfaction acting as a mediating variable. In a highly competitive Islamic banking industry, an effective marketing strategy is essential for sustaining customer loyalty. This research employs a quantitative approach, using purposive sampling of 100 customers from five BSI branches in Banda Aceh. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression and path analysis. The results indicate that while factors such as place, human resources, and physical evidence contributed to customer loyalty, ineffective promotion and slow service processes reduced it. Furthermore, customer satisfaction plays a mediating role, strengthening the link between the marketing mix and loyalty. These findings emphasize the need for BSI Banda Aceh Branch to improve their service efficiency, enhance human resource quality, and adopt more targeted promotional strategies to retain customers in the long term. Enhancing service efficiency and refining marketing strategies will allow BSI Banda Aceh to maintain a competitive edge in the evolving Islamic banking industry.